2016
DOI: 10.1002/mus.25190
|View full text |Cite
|
Sign up to set email alerts
|

Single amino acid loss in the dystrophin protein associated with a mild clinical phenotype

Abstract: The c.5068_5070delCAC locus in the DMD gene is associated with a very mild phenotype. Further study is needed to evaluate disease progression in these patients. Muscle Nerve 55: 46-50, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…The haplotype study in our series revealed that all index case groups harboring the same BP originated from distinct founder mutations, except for the D1 group, which turned out to be the result of 2 independent founder mutation events. The high rate of founder effects observed in our series contrasts with their rare occurrence in the BMD disease population, as only 2 similar founder effects occur have been reported 43,44 . In any case, this phenomenon is indicative of the preservation of fertility.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The haplotype study in our series revealed that all index case groups harboring the same BP originated from distinct founder mutations, except for the D1 group, which turned out to be the result of 2 independent founder mutation events. The high rate of founder effects observed in our series contrasts with their rare occurrence in the BMD disease population, as only 2 similar founder effects occur have been reported 43,44 . In any case, this phenomenon is indicative of the preservation of fertility.…”
Section: Discussioncontrasting
confidence: 65%
“…The high rate of founder effects observed in our series contrasts with their rare occurrence in the BMD disease population, as only 2 similar founder effects occur have been reported. 43,44 In any case, this phenomenon is indicative of the preservation of fertility. On the other hand, this observation provided us with the chance to dispose of groups with sufficient size to enable the comparison of the effect of BP locations on the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the frequently reported cases, the simple insertion or substitution mutations are more likely to resided in different Spectrins repeats within the Central Rod domain (Fig. 5c) [40][41][42], indicating that the possible significant anchoring or binding functions are important for maintaining the abundance and activity of dystrophy. Indeed, Multiple-polymorphic sites were found within the coding region of DMD and the reduced expression level of dystrophin is associated with the incidence of DMD [43].…”
Section: Discussionmentioning
confidence: 98%